Evaluation of dietary acidifiers on growth performance of nursery pigs - Nemechek, J. E.; Tokach, Michael D.; Dritz, Steven S.; Goodband, Robert D.; DeRouchey, Joel M.; Bergstrom, J. R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
Three 28-d experiments were conducted to determine the effects of dietary acidifiers on the growth performance of nursery pigs housed under both university and field conditions. All diets were corn-soybean meal–based and fed in meal form. Each experiment consisted of a 2-phase diet series with decreasing nutrient concentrations in the second phase. The same 4 dietary treatments were evaluated in all 3 experiments, including a control with (1) no acidifier, (2) 0.5% Vevovitall (DSM Nutritional Products, Parsippany, NJ), (3) 0.2% Kem-Gest (Kemin Americas, Des Moines, IA), or (4) 0.05% Buti- Pearl (Kemin Americas). In Exp. 1, 280 weanling pigs (PIC 327 × 1050, initially 16.1 lb, 3 d postweaning) were used with 7 pigs per pen and 10 pens per treatment. From d 0 to 14, pigs fed the Kem-Gest diet tended to have increased (P < 0.07) ADG compared with pigs fed the other 3 treatments. From d 14 to 28 and for the overall data (d 0 to 28), no differences (P > 0.64) were observed in ADG, ADFI, or F/G among treatments. In Exp. 2, 1,728 nursery pigs (PIC 327 × 1050, initially 12.8 lb, 10 d postweaning) were used with 48 pigs per feeder (24 pigs per pen) and 9 feeders per treatment. Treatment diets were fed from d 0 to 14, and a common diet was fed from d 14 to 28. From d 0 to 14, pigs fed the control diet had decreased (P < 0.001) ADG and poorer (P < 0.001) F/G compared with pigs fed diets with acidifiers. From d 14 to 28, when a common diet was fed, there were no differences (P > 0.60) in ADG, ADFI, or F/G among treatments. Overall (d 0 to 28), there were no differences in ADG, ADFI, or F/G (P > 0.11), but pigs fed diets containing acidifiers were approximately 2 lb heavier at the conclusion of the trial. In Exp. 3, 1,800 nursery pigs (PIC 327 × 1050, initially 16.3 lb, 13 d postweaning) were used with 50 pigs per feeder (25 pigs per pen) and 9 feeders per treatment. Treatment diets were fed throughout the entire trial (d 0 to 28), but there were no differences (P > 0.12) in ADG, ADFI, or F/G among pigs fed the different dietary treatments from d 0 to 14, d 14 to 28, or for the overall trial. Overall, the responses to dietary acidification were inconsistent across experiments, but the reasons are unclear. Pigs fed acidifiers had improved growth performance in Exp. 2, but not Exp. 1 and 3. Further research is needed to determine the reason for the inconsistent responses so dietary acidifiers can be used effectively to improve the performance of nursery pigs.
Keywords: Acidifiers; Benzoic acid; Butyric acid; Nursery pig